State of Body Bioimpedance Parameters After Massage Therapy - Mohamad, Mohd Riduan; Wan Ibrahim, Wan Mohd Azhar (International Journal of Integrated Engineering, 2022)
Massage therapy is a commonly non-invasive; economical; comforting; not has side effects and greatly appreciated by recipients. The Bioelectrical Impedance Analysis (BIA) method is identified as one of the quick, simple and safest non-invasive techniques to measure the body bioimpedance parameters after doing massage therapy. The male bioimpedance parameters were measured before and after massage therapy by using the Microtest 6378 Impedance Analyzer. The measured bioimpedance parameters were Capacitance (C); Phase Angle (Î¸), Impedance (Z); Resistance (R) and Reactance (X). The other body composition parameters were then calculated including Basal Metabolic Rate (BMR); Fat Mass (FM); Fat Free Mass (FFM); Total Body Water (TBW); Intracellular Water (ICW) and Extracellular Water (ECW). The measurements of bioimpedance and body composition parameters were significantly different before and after massage therapy. In addition, the massage therapy increased the C; Î¸; Z; R; X; FM; and ICW. However, the massage therapy also decreased the BMR; FFM; TBW and ECW. This study shows that the BIA technique can obtain the male body bioimpedance parameters safely and accurately.